A simple and convenient synthesis of 3-arylpyran-2-ones via the Meerwein reaction. Issue 1 (6th January 2016) - Lytvyn, Roman Z.; Neshchadin, Andriy O.; Pitkovych, Khrystyna Ye.; Horak, Yuriy I.; Grazulevicius, Juozas V.; Lis, Tadeusz; Kinzhybalo, Vasyl; Obushak, Mykola D.
Graphical abstract: Abstract: A simple and practical procedure was proposed for the synthesis of 3-arylpyran-2-ones from the reaction of pyran-2-ones and arenediazonium chlorides under Meerwein reaction conditions.